2019
DOI: 10.3390/en12193742
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Optimization of CO2-to-Methanol with Solid-Oxide Electrolyzer

Abstract: Carbon capture and utilization are promising to tackle fossil-fuel depletion and climate change. CO2 hydrogenation can synthesize various chemicals and fuels, such as methanol, formic acid, urea, and methane. CO2-to-methanol integrated with solid-oxide electrolysis (SOE) process can store renewable power in methanol while recycling recovered CO2, thus achieving the dual purposes of storing excess renewable power and reducing lifetime CO2 emissions. This paper focuses on the techno-economic optimization of CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Finally, when looking at ASPEN process simulations, a similar trend is again observed with most of the works being done in the methanol pathway field, probably owing to the easier downstream separation of this process . Here, a typical process comprises an initial feed with pressurization steps followed by a fixed bed reactor.…”
Section: Process Design Considerationssupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, when looking at ASPEN process simulations, a similar trend is again observed with most of the works being done in the methanol pathway field, probably owing to the easier downstream separation of this process . Here, a typical process comprises an initial feed with pressurization steps followed by a fixed bed reactor.…”
Section: Process Design Considerationssupporting
confidence: 57%
“…280 The simulation results showed that in the adiabatic and the gas-cooled reactor the hot spot temperatures inside the system can be within the typical operating temperature range for the catalyst and only the water-cooled system showed advantages in terms of efficient heat removal. Finally, when looking at ASPEN process simulations, a similar trend is again observed [281][282][283][284][285][286][287] with most of the works being done in the methanol pathway field, 281-285 probably owing to the easier downstream separation of this process. 286 Here, a typical process comprises an initial feed with pressurization steps followed by a fixed bed reactor.…”
Section: Process Design Considerationssupporting
confidence: 54%
“…Furthermore, the carbon dioxide for the methanol synthesis was provided by the oxyfuel combustion biomass gasification system. Zhang et al [7] studied the techno-economic optimization of green methanol production from the carbon dioxide hydrogenation system with an integrated solid-oxide electrolysis process. They simulated the system using Aspen Plus and used multi-objective optimization for the techno-economic optimization.…”
Section: Introductionmentioning
confidence: 99%
“…To commercialize green MeOH production, the realization of MeOH parity (which is when green MeOH production cost is compared favorably with that of gray MeOH production) should be conducted. Hence, several studies dealing with techno-economic analysis (TEA) for green MeOH production have been reported to calculate the unit MeOH production cost at a certain point in time, as shown in Figure . …”
Section: Introductionmentioning
confidence: 99%